Paraphrase or plagiarism? Exploring EAP students’ use of source material in a transnational university context (Journal of Applied Learning and Teaching, 2024)
The relationship between paraphrase and plagiarism is complex and has been the subject of multiple research studies. However, recent advances in Generative AI (GenAI) have disrupted the standard practices of academic writing and established a renewed focus on how learners acquire skills in English writing in a higher education context. To understand the future of academic writing in the technological era, further investigation of how and why students choose to paraphrase and engage with source material is needed to guide best practices in instruction, policy, and research. This exploratory study seeks to fill this gap and provide insight into the choices English as a Second Language (ESL) student writers make in an English for Academic Purposes (EAP) context. Using a text-based interview method and custom-designed academic writing task, we examine how students engage with and make decisions about using source material. Results reveal that participants focus more on sentence-level approaches to paraphrasing and mechanistic methods of language transformation. This is partly motivated by prior learning experiences but may also be related to adopting a risk-averse approach to language use to avoid accusations of plagiarism. Furthermore, our participants expressed a low level of confidence in the ability of new technological tools to help learners acquire skills in English writing. These findings suggest that there is a need for further research exploring policies to enable experimentation in EAP programs, as well as exploring acceptance and belief in new technologies’ ability to support paraphrasing and source use.